A study on small and medium scale industries (SMI): Focus on incubator program Introduced by SRIM Berhad / Amielda Ibrahim - Ibrahim, Amielda (Faculty of Business and Management, 2002)
The aim of this research is to study the effectiveness of the incubator program offered by SIRIM Berhad to all small and medium entrepreneurs in Malaysia. This study is based on information from interviews and questionnaires. This report outlined the findings, analysis and recommendation based on the questionnaire distributed to the respondents. Most of the respondents were asked about their perception and opinion on satisfaction and dissatisfaction about the incubator scheme.